Alexandre Popov's Full Stroke at 35 m of His 50 m Silver Medal Race at the 1998 Perth World Championships - Rushall, B. S.
Video pictures and the appropriate technical/ biomechanical explanations for Alexandre Popov's Full Stroke at 35 m of His 50 m Silver Medal Race at the 1998 Perth World Championships. This sequence of 18 frames shows Alexandre Popov sprinting hard. His development of continuous force application (the "kayak principle") and the use of thehand/forearm-propelling surface supported on a streamlined posture are very notable features of his stroke and are worthy of emulation. What also is remarkable in this sequence is the number of "current" coaching theories and technique features that are not exhibited. It dispels much of today's freely-dispensed misinformation.